Bone metastasis target redox-responsive micell for the treatment of lung cancer bone metastasis and anti-bone resorption. (31st October 2018) - Ye, Wei-Liang; Zhao, Yi-Pu; Cheng, Ying; Liu, Dao-Zhou; Cui, Han; Liu, Miao; Zhang, Bang-Le; Mei, Qi-Bing; Zhou, Si-Yuan
Abstract: In order to inhibit the growth of lung cancer bone metastasis and reduce the bone resorption at bone metastasis sites, a bone metastasis target micelle DOX@DBMs-ALN was prepared. The size and the zeta potential of DOX@DBNs-ALN were about 60 nm and −15 mV, respectively. DOX@DBMs-ALN exhibited high binding affinity with hydroxyapatite and released DOX in redox-responsive manner. DOX@DBMs-ALN was effectively up taken by A549 cells and delivered DOX to the nucleus of A549 cells, which resulted in strong cytotoxicity on A549 cells. The in vivo experimental results indicated that DOX@DBMs-ALN specifically delivered DOX to bone metastasis site and obviously prolonged the retention time of DOX in bone metastasis site. Moreover, DOX@DBMs-ALN not only significantly inhibited the growth of bone metastasis tumour but also obviously reduced the bone resorption at bone metastasis sites without causing marked systemic toxicity. Thus, DOX@DBMs-ALN has great potential in the treatment of lung cancer bone metastasis. Graphical Abstract: UF0001